Decomposing the variance in early maladaptive schemas: the major role of one general factor, the minor role of domains, and their differential relations to facial emotion recognition - Tabesh, Sajedeh; Zia-Tohidi, Ali; Firoozi, Manijeh; Farahani, Hojjatollah (Frontiers in Psychology, 2024)
Evidence is growing rapidly on the role of early maladaptive schemas (EMSs) in different aspects of our mental life. Some suggest their impact on facial emotion recognition, which can widely affect our social interactions. However, evidence accumulation in these paths is decelerated by a lack of clear understanding of the structure of schemas. Different sets of scores are calculated from the schema questionnaire without a solid ground or even a clarified meaning. Here we explain that the schema variance can be theoretically decomposed into three components: schema-specific, domain-specific due to the unmet core needs, and the common variance due to the general vulnerability; each can differentially correlate with other substantive variables. Using this framework, we empirically investigated the structure of schemas (N = 259); then how it relates to facial emotion recognition. A general factor explained 27%, 40%, and 64% of the total variance in items, schemas, and domains, respectively, proving strong support for a general susceptibility factor. Partialling out the common variance, there was little domain-specific variance left, suggesting that domain scores may be unreliable or even misleading. Regarding facial emotion recognition, they were not correlated with schemas; however, the general susceptibility factor was correlated with anger recognition.